Sistem Agenda Kegiatan Program Studi Sistem Informasi Berbasis Web - Ega Syifa Fauziah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Kalbis Institute of Technology and Business is an institute in Jakarta which has two faculties, namely: the Faculty of Creative Industry and the Faculty of Business. For example, the Faculty of Creative Industry has an Information Systems Study Program. Each year, the information system study program plans an annual budget and work program that must be executed. The problem that often occurs in this study program is that sometimes the work is quite large and the burden is quite a lot, so that the activities that must be done by the lecturer are often forgotten. Researchers make an activity agenda system which is expected to help lecturers in reminding activities that can be executed on time. System is created use Hypertext Preprocessor (PHP) programming language, the system development method uses Prototyping, and the system testing uses Black Box Testing. The final result of this research is a system of lecturers activities agenda that is used to add to the agenda of activities carried out by the Chair of the study program, view the agenda of activities and provide notification of activity agenda in the form of pop-ups in the system